An evolving perspective on the Pseudomonas aeruginosa orphan quorum sensing regulator QscR - Chugani, Sudha; Greenberg, Everett P. (Frontiers in Cellular and Infection Microbiology, 2014)
Many Proteobacteria govern responses to changes in cell density by using acyl-homoserine lactone (AHL) quorum-sensing (QS) signaling. Similar to the LuxI-LuxR system described in Vibrio fischeri, a minimal AHL QS circuit comprises a pair of genes, a luxI-type synthase gene encoding an enzyme that synthesizes an AHL and a luxR-type AHL-responsive transcription regulator gene. In most bacteria that utilize AHL QS, cognate luxI and luxR homologs are found in proximity to each other on the chromosome. However, a number of recent reports have identified luxR homologs that are not linked to luxI homologs; in some cases luxR homologs have been identified in bacteria that have no luxI homologs. A luxR homolog without a linked luxI homologs is termed an orphan or solo. One of the first reports of an orphan was on QscR in Pseudomonas aeruginosa. The qscR gene was revealed by whole genome sequencing and has been studied in some detail. P. aeruginosa encodes two AHL synthases and three AHL responsive receptors, LasI-LasR form a cognate synthase-receptor pair as do RhlI-RhlR. QscR lacks a linked synthase and responds to the LasI-generated AHL. QS regulation gene regulation in P. aeruginosa employs multiple signals and occurs in the context of other interconnected regulatory circuits that control diverse physiological functions. QscR affects virulence of P. aeruginosa, and although it shows sensitivity to the LasI-generated AHL, 3-oxo-dodecanoylhomoserine lactone, it’s specificity is relaxed compared to LasR and can respond equally well to several AHLs. QscR controls a set of genes that overlaps the set regulated by LasR. QscR is comparatively easy to purify and study in vitro, and has become a model for understanding the biochemistry of LuxR homologs. In fact there is a crystal structure of QscR bound to the LasI-generated AHL. Here, we review the current state of research concerning QscR and highlight recent advances in our understanding of its structure and biochemistry.